Few geographic and socioeconomic variations exist in primary total shoulder arthroplasty: a multi-level study of Australian registry data. Issue 1 (December 2016) - Brennan-Olsen, Sharon; Page, Richard; Lane, Stephen; Lorimer, Michelle; Buchbinder, Rachelle; Osborne, Richard; Pasco, Julie; Wluka, Anita; Sanders, Kerrie; Ebeling, Peter; Graves, Stephen
Abstract Background Associations between socioeconomic position (SEP) and the uptake of primary total shoulder arthroplasty (TSA) is not well understood in the Australian population, thus potentially limiting equitable allocation of healthcare resources. We used the Australian Orthopaedic Association National Joint Replacement Registry (AOA NJRR) to examine whether geographic or socioeconomic variations exist in TSA performed for a diagnosis of osteoarthritis 2007–11 for all Australians aged ≥40 years. Methods Primary anatomical and reverse TSA data were extracted from the AOA NJRR which captures >99 % of all TSA nationally. Residential addresses were cross-referenced to Australian Bureau of Statistics 2011 Census data to identify SEP measured at the area-level (categorised into deciles), and geographic location defined as Australian State/Territory of residence. We used a Poisson distribution for the number of TSA over the study period, and modelled the effects of age, SEP and geographic location using multilevel modelling. Results During 2007–11, we observed 6, 123 TSA (62.2 % female). For both sexes, TSA showed a proportional increase with advancing age. TSA did not vary by SEP or geographic location, with the exception of greater TSA among men in New South Wales. Conclusions Using a national registry approach we provide the first reliable picture of TSA at a national level. The uptake of TSA was equitable across SEP; however, there was some variation between the States/Territories. With an aging population, it is imperative that monitoring of major surgical procedures continues, and be focused toward determining whether TSA uptake correlates with need across different social and area-based groups.